Relationship between Knowledge and Attitudes of Parents About IPV ( Inactivated Poliovirus Vaccine)Immunization at the Age of 4 – 18 Months - Erna Rahmawati (Journal of Global Research in Public Health, 2023)
Parents' knowledge and attitudes about  Inactivated Poliovirus Vaccine IPV immunization are very important to improve children's health status. Children under 5 years old are a vulnerable phase to disease and vulnerable to death caused by viruses. This study aims to determine whether there is a relationship between knowledge and attitudes of parents about immunization ipv at age 4 – 18 months. This study uses a correlation analytic method with a cross sectional approach. The sampling technique used accidental sampling on mothers of babies who came for IPV immunization and obtained a sample of 42 respondents. How to get data by distributing questionnaires, the data analysis technique used the Spearman Rank correlation test. Out of 42 respondents, the results of the study obtained good knowledge of 15 respondents and showed positive attitude of 24 respondents, and 24 respondents with sufficient knowledge with a negative attitude of 18 respondents. Spearman Rank correlation test obtained significant results of 0.000 <0.05 which means there is a relationship between knowledge and attitudes of parents about IPV immunization at the age of 4-18 months.